The Political and Economic Impact of Formula 1 Races in Azerbaijan: Myths and Realities - Gubad Ibadoghlu (SSRN, 2024)
Since 2016, Azerbaijan has been hosting the Formula 1 Grand Prix. Due to COVID-19, the race was not held in 2020 and was conducted without spectators in 2021. The initial contract for the event was supposed to end in 2020, but it was extended for another three years. In 2023, Azerbaijan secured the continuation of its hosting rights until at least 20261. Apart from Formula 1, the country has hosted several other prestigious international events, including the Eurovision Song Contest in 2012, the first European Olympic Games in 2015, the 4th Islamic Solidarity Games in 2017, and the European Youth Olympic Festival in 2019. In 2024, Azerbaijan will host COP29, the most significant event in its history since independence, further adding to its diverse event portfolio. Despite some questions surrounding Baku's role as a host for Formula 1 compared to other international sports events, the Azerbaijani government has regularly organized the race for the past seven years and has yet to address these questions. The 2024 Formula 1 Azerbaijan Grand Prix is scheduled to take place again in Baku from September 13 to 15. In this paper, we examine the myths and realities regarding the economic impact of Formula 1 races.
Keywords: 330